Built to last : successful habits of visionary companies - Collins, James C. (James Charles), 1958-; Porras, Jerry I (New York : HarperBusiness, 1994)
"This is not a book about charismatic visionary leaders. It is not about visionary product concepts or visionary products or visionary market insights. Nor even is it about just having a corporate vision. This is a book about something far more important, enduring, and substantial. This is a book about visionary companies." So write James C. Collins and Jerry I. Porras in this groundbreaking book that shatters myths, provides new insights, and gives practical guidance to those who would like to build landmark companies that stand the test of time
Drawing upon a six-year research project at the Stanford University Graduate School of Business, Collins and Porras took eighteen truly exceptional and long-lasting companies - they have an average age of nearly one hundred years and have outperformed the general stock market by a factor of fifteen since 1926 - and studied each company in direct comparison to one of its top competitors. They examined the companies from their very beginnings to the present day - as start-ups, as midsize companies, and as large corporations. Throughout, the authors asked: "What makes the truly exceptional companies different from other companies?"
By answering such questions, Collins and Porras go beyond the incessant barrage of management buzzwords and fads of the day to discover timeless qualities that have consistently distinguished outstanding companies. They also provide inspiration to all executives and entrepreneurs by destroying the false but widely accepted idea that only charismatic visionary leaders can build visionary companies. Filled with hundreds of specific examples and organized into a coherent framework of practical concepts that can be applied by managers and entrepreneurs at all levels, Built to Last provides a master blueprint for building organizations that will prosper long into the twenty-first century and beyond
The best of the best -- Clock building, not time selling -- More than profits -- Preserve the core/stimulate progress -- Big hairy audacious goals -- Cult-like cultures -- Try a lot of stuff and keep what works -- Home-grown management -- Good enough never is -- The end of the beginning -- Building the vision
Includes bibliographical references (pages 305-333) and index
Keywords: Success in business -- United States; Industrial management -- United States; Entrepreneurship -- United States